Identification and antibiotic resistance of enterococcus (Schleifer and Kilper-Balz 1984) species isolated from Iloilo River - Ansino, Jan Reygine G.
The presence Enterococci species in the water has long been regarded as an indicator of fecal contamination. With the increasing rate of antimicrobial resistance globally, infections caused by enterococcal species became difficult to treat. The study determined the species distributions and antimicrobial resistance profiles of Enterococcus species isolated from water and sediment samples in the Iloilo River. Susceptibility of the isolates was tested against: ampicillin, penicillin, ciprofloxacin, chloramphenicol, doxycycline, erythromycin, tetracycline, and vancomycin. Among the 115 fecal coliform samples, a total of 61 (53 percent) isolates were confirmed to belong to the genus Enterococcus. Of these, 40 percent were identified as Enterococcus faecalis, followed by Enterococcus faecium 33 percent and Enterococcus avium (4 percent). Isolates showed resistance to tetracycline (51 percent), erythromycin (18 percent) and doxycycline (13 percent) and a high level susceptibility to ampicillin (100 percent) chloramphenicol (93 percent) and penicillin (90 percent). Multiple antibiotic resistance patterns revealed resistance to at least four antibiotics. Six (12 percent) vancomycin-resistant Enterococci (VRE) were detected. The results revealed low level of antibiotic resistance in the river. However, the presence of these fecal contaminats in the river can still pose a potential risk to the humn health and the spread of antibiotic resistance genes indicating a great importance in improving risk management practices in the river.